Current technology on nutrients removal, recovery and reuse from liquid fraction of digestate - Akhiar A.; Zamri M.F.M.A.; Torrijos M.; Battimelli A.; Roslan E.; Hanif M.; Shamsuddin A.H.; Carrere H. (Mattingley Publishing, 2023)
Ammonia; Anaerobic digestion; Bioethanol; Calcium compounds; Chlorine compounds; Commerce; Cultivation; Distillation; Fertilizers; Liquids; Magnesium compounds; Marketing; Nitrogen removal; Potassium; Recycling; Sludge digestion; Sodium compounds; Stripping (removal); Sulfur compounds; Vacuum evaporation; Wastewater treatment; Wetlands; Agricultural sector; Anaerobic ammonium oxidation; Bio-ethanol production; Biomass productions; Constructed wetlands; Direct contact membrane distillation; Recovery technology; Solid liquid separation; Nutrients